Natural Versus National Boundaries: the Importance of Considering Biogeographical Patterns in Forest Conservation Policy. Issue 1 (13th February 2014) - Gustafsson, Lena; Felton, Adam; Felton, Annika M.; Brunet, Jörg; Caruso, Alexandro; Hjältén, Joakim; Lindbladh, Matts; Ranius, Thomas; Roberge, Jean‐Michel; Weslien, Jan
Abstract Applying biogeographical insights to the regulation of production forestry and the determination of forest reserve strategies is expected to increase the effectiveness of biodiversity conservation actions. Here, we assess the extent to which such applications take place. By using Sweden as a case study, we demonstrate fundamental differences among biogeographical regions in natural patterns and processes, past land‐use, and anthropogenic impacts that need to be better incorporated into strategic conservation planning and decisions. Furthermore, assessment of specific forestry regulations and biogeographical variation in a number of other countries/provinces embracing boreal and temperate biomes also indicate that natural boundaries are insufficiently considered in forest management policies. We suggest that a substantial potential exists to better align conservation priorities with biogeographical characteristics. To illustrate the application of such an approach, we present a decision support model on how forest conservation policies that rest on natural boundaries and ecological processes can be developed.